Guidonia: town of air and flight (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
In the ranks of the foundation cities of Lazio we have repeatedly noted how Guidonia represents an interesting anomaly. Out of the characters of the Mediterranean modernism of the foundation cities settled in the Pontine Plain, the new city was created to support one of the most important scientific centers for aeronautics. The housing units and the main public building represent typological experiments (terraced houses), designed by Giuseppe Nicolosi and Giorgio Calza Bini.Â